BIOCHEMICAL MARKERS OF RENAL DYSFUNCTIONS IN CRITICALLY ILL FULL - TERM NEWBORNS - A. Babintseva (Ukrainian Journal of Nephrology and Dialysis, 2015)
Introduction. Full - term newborns with clinical signs of severe perinatal pathology constitute a high risk group of the formation of urinary system functional disorders, the diagnostic of which in the early neonatal period is complicated.Objective of the research was to study the condition of renal functions in critically ill full - term newborns during the first week of their life by means of detection of specific biomarkers level in the blood serum and urine.Materials and methods. A comprehensive clinical - paraclinical examination of 36 critically ill newborns (the main group) and 37 conditionally healthy newborns (the control group) has been conducted. Laboratory methods ofexamination included detection of the levels of creatinine, urea, sodium and potassium ions in the blood and urine, as well as protein, albumin, immunoglobulin G, a - - microglobulinand $ - microglobulinin urine.Results and discussion. The neonates of the main group as compared to the control one presented statistically significant higher levels of creatinine (р<0,01) and urea (р<0,001) in the blood serum against the ground of lower glomerular filtration rate (р<0,05) and the level ofpotassium ions (р<0,01); in the urine — statistically significant lower level of creatinine (р<0,01), higher levels of urea (р<0,001) and sodium ions (р<0,05). Evaluation of urineproteinogramin the main group of newborns as compared to the control group enabled to find statistically significant higher levels of protein (р<0,01), albumin (р<0,01), immunoglobulin G (р<0,05), a - - microglobulin (р<0,01), $ - - microglobulin (р<0,01).Conclusions. Critically ill full - term newborns with perinatal pathology receiving treatment in the Intensive Care Unit are under conditions of a complex influence of potentially nephrotoxic factors (hypoxia, reoxygenation - reperfusion, infection, artificial lung ventilation, infusion, inotropic, transfusion and antibacterial therapy). Severity of general condition, morpho - functional immaturity of the organism, multiple organ failure due to underlying perinatal pathology “obscure” renal symptoms and complicate the diagnostics of renal function disorders. The biochemical changes found in critically ill newborns require timely diagnostics to correct therapeutic measures on the stage of intensive therapy with the aim to prevent the development of severe renal pathology and chronic renal failure in future.